ISU GENDER PADA TOKOH PEREMPUAN DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU - Ruaidah Ruaidah (Universitas Islam Negeri Imam Bonjol Padang, 2012)
This writing is done to know how for the gender issues affects the female characters in the novel Nayla of Djenar Maesa Ayu. The effect of inequality will appears subordination and violence against to women. Subordination and violence are events that affects the female characters in the novel Nayla of Djenar Maesa Ayu. The author tries to raise the position of women from gender inequality. The figure of Nayla tries to find the self-awareness and the existence of gender inequality. Keywords : Gender, subordination, and violenceCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i2.54